Metagenomic analysis reveals the effects of long-term antibiotic pressure on sludge anaerobic digestion and antimicrobial resistance risk. (June 2019) - Xu, Rui; Yang, Zhao-Hui; Zheng, Yue; Wang, Qing-Peng; Bai, Yang; Liu, Jian-Bo; Zhang, Yan-Ru; Xiong, Wei-Ping; Lu, Yue; Fan, Chang-Zheng
Highlights: Metagenomic approach revealed the effects of antibiotics on anaerobic digestion. Antibiotics impacted archaeal community and genes encoding fatty acid degradation. All methanogenesis pathways were influenced by antibiotics pressure. Antibiotics increased the antimicrobial resistant risks of digested sludge. Positive association among antibiotics, ARG and specific microbe were found. Abstract: Continuous stirred-tank digesters with tetracyclines and sulfonamides were operated to investigate the impacts of antibiotic pressure on sludge anaerobic digestion. The versatile methanogen Methanosarcinales and strictly hydrogenotrophic methanogen Methanobacteriales increased and decreased by 21.1% and 10.9% under antibiotic pressure, respectively. KEGG analysis revealed that hydrogenotrophic and acetoclastic methanogenesis pathways were all affected. The decrease in abundance of function genes involved in lipid metabolism, carbohydrate metabolism, and fatty acid degradation, would lead to a reduction in methane production by 25%. Network analysis indicated positive associations among tetracycline residuals, abundance of resistance genes (ARGs), and specific member of potential hosts. Over 1000 ARG subtypes were widely detected in sludge, including macrolide (28%), tetracycline (24%), fluoroquinolone (20%), and peptide (20%) resistance genes. AD process exposed to long-term antibiotic would increase the diversity and abundance of ARG, enhance the association of ARG with specific microbes, and select bacteria able to perform chemotaxis mechanism.